An evaluation of Admedus' tissue engineering process-treated (ADAPT) bovine pericardium patch (CardioCel) for the repair of cardiac and vascular defects. (March 2014) - Strange, Geoff; Brizard, Christian; Karl, Tom R; Neethling, Leon
Abstract : Tissue engineers have been seeking the 'Holy Grail' solution to calcification and cytotoxicity of implanted tissue for decades. Tissues with all of the desired qualities for surgical repair of congenital heart disease (CHD) are lacking. An anti-calcification tissue engineering process (ADAPT ® TEP) has been developed and applied to bovine pericardium (BP) tissue (CardioCel ®, AdmedusRegen Pty Ltd, Perth, WA, Australia) to eliminate cytotoxicity, improve resistance to acute and chronic inflammation, reduce calcification and facilitate controlled tissue remodeling. Clinical data in pediatric patients, and additional pre-market authorized prescriber data demonstrate that CardioCel performs extremely well in the short term and is safe and effective for a range of congenital heart deformations. These data are supported by animal studies which have shown no more than normal physiologic levels of calcification, with good durability, biocompatibility and controlled healing.